2021
DOI: 10.1108/tqm-09-2020-0203
|View full text |Cite
|
Sign up to set email alerts
|

Examining antecedents and consequences of perceived service quality in the hotel industry: a comparison between London and New York

Abstract: Purpose This paper aims at exploring the relations amongst the concepts of customer relationship management (CRM), convenience, trust, perceived service quality, satisfaction, perceived value, loyalty, image and purchase intention in the hotel sector.Design/methodology/approach The research was conducted using interviews with hospitality managers and guests who had a direct connection with the hotel industry. According to the qualitative study results and literature review, the authors designed a model that wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 137 publications
(199 reference statements)
1
10
0
3
Order By: Relevance
“…Authors in [33] discussed service quality from within self-determination theory in mobile banking. Authors in [58] examined the antecedents and consequences of perceived SRQ in the hotel industry, whilst [76] studied consumption value of m-banking services. In addition, [77] studied system and service qualities with customer satisfaction.…”
Section: Theory Of Planned Behavior (Tpb) and Technology Acceptance M...mentioning
confidence: 99%
“…Authors in [33] discussed service quality from within self-determination theory in mobile banking. Authors in [58] examined the antecedents and consequences of perceived SRQ in the hotel industry, whilst [76] studied consumption value of m-banking services. In addition, [77] studied system and service qualities with customer satisfaction.…”
Section: Theory Of Planned Behavior (Tpb) and Technology Acceptance M...mentioning
confidence: 99%
“…In addition to eight independent factors, the study suggested 4 moderating factors that influence the intermediate variable attitude towards SAND App The moderating factors suggested are age, education level, gender, and internet experience. The moderating factors were developed based on many previous studies and suggested in the UTAUT original model [ 7 , 28 , 46 ].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Perceived service quality defined as the variation between the expected services and perceptions of the actual service provided. According to [7,20,37,38] service quality has many standards that can be grouped into 5 dimensions "tangibles (SQT), reliability (SQR), responsiveness (SQP), assurance (SQA), and empathy (SQE)". Previous research has shown that Perceived Service Quality (PSQ) has a noteworthy influence on behavioral intentions to use e-government services and to recommend the adoption of e-government services [3,25,39].…”
Section: H7 Trust In Sanad App (Ti) Has a Positive Influence Related ...mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, satisfaction based on perceived value has been established as a strong driving force for the creation of trust (Dayan et al. , 2022; Han and Hyun, 2015; Palazzo et al. , 2021; Shin and Jeong, 2022; Wu et al.…”
Section: Literature Reviewmentioning
confidence: 99%